2019
DOI: 10.1038/s41467-019-09721-w
|View full text |Cite
|
Sign up to set email alerts
|

Ecological and geographical overlap drive plumage evolution and mimicry in woodpeckers

Abstract: Organismal appearances are shaped by selection from both biotic and abiotic drivers. For example, Gloger’s rule describes the pervasive pattern that more pigmented populations are found in more humid areas. However, species may also converge on nearly identical colours and patterns in sympatry, often to avoid predation by mimicking noxious species. Here we leverage a massive global citizen-science database to determine how biotic and abiotic factors act in concert to shape plumage in the world’s 230 species of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

6
72
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(79 citation statements)
references
References 68 publications
6
72
1
Order By: Relevance
“…In fact, interspecific comparative analyses are crucial to revealing how evolutionary processes operating within species can be generalized across macroevolutionary scales (Meiri 2011, Stoddard et al 2019). The predicted negative correlation between brightness and humidity has been supported in phylogenetic comparative studies of the world’s primates (Kamilar and Bradley 2011), a large clade of Holartic shrews (Stanchak and Santana 2018), the entire Australian avifauna (Delhey 2018), the world’s woodpeckers (Miller et al 2019), and the world’s passerine birds (Delhey et al 2019). The latter two studies also supported the prediction of Bogert’s rule that animals are lighter in warmer regions.…”
mentioning
confidence: 86%
“…In fact, interspecific comparative analyses are crucial to revealing how evolutionary processes operating within species can be generalized across macroevolutionary scales (Meiri 2011, Stoddard et al 2019). The predicted negative correlation between brightness and humidity has been supported in phylogenetic comparative studies of the world’s primates (Kamilar and Bradley 2011), a large clade of Holartic shrews (Stanchak and Santana 2018), the entire Australian avifauna (Delhey 2018), the world’s woodpeckers (Miller et al 2019), and the world’s passerine birds (Delhey et al 2019). The latter two studies also supported the prediction of Bogert’s rule that animals are lighter in warmer regions.…”
mentioning
confidence: 86%
“…Ornamental traits might be used in competitive interactions or in sexual displays. For this reason, 65 many studies have explored how sexual and social interactions may have driven plumage colour evolution 66 (Dale et al, 2015;Dunn, Whittingham, & Pitcher, 2001;Miller et al, 2019;Møller & Birkhead, 1994;67 Owens & Hartley, 1998;Rubenstein & Lovette, 2009). Colour traits can be favoured by sexual selection 68 if the expression of the trait increases the reproductive success of individuals by gaining more access to 69 mates, or by social selection if their expression is critical in the competition for social status or access to 70 resources such as food or territories (West-Eberhard, 1983).…”
mentioning
confidence: 99%
“…Furthermore, the slow-fast life-history continuum is related to 112 extra-pair paternity: species with higher adult mortality rates and larger clutch sizes have higher levels of 113 extra-pair paternity (Arnold & Owens, 2002). 114 6 Different studies have evaluated how abiotic factors affect bird plumage colour evolution and a 115 variety of hypotheses have been proposed to explain colour variation both within and across avian taxa 116 (Dale et al, 2015;Miller et al, 2019;Ribot, Berg, Schubert, Endler, & Bennett, 2019). Previous studies 117 showed that achromatic (light-to-dark) variation in birds is related to climate variables such as 118 temperature and precipitation (Delhey, 2017(Delhey, , 2018(Delhey, , 2019Heidrich et al, 2018;Miller et al, 2019;119 Pinkert, Brandl, & Zeuss, 2017;Ribot et al, 2019).…”
mentioning
confidence: 99%
“…There are numerous examples of phenotypic convergence among birds [7][8][9][10][11][12][13][14][15], and several authors 66 have proposed hypotheses to explain this phenomenon in the context of mimicry [7,13,[16][17][18][19][20][21][22].…”
mentioning
confidence: 99%
“…Although convergence in plumage patterns is widespread across birds [7,8,[10][11][12][13][16][17][18][19]21,55], few 280 studies have assessed the mechanisms underlying this phenomenon. For example, convergence has been 281 documented in birds which may engage in mimicry including toucans [56], friarbirds and orioles [8], and 282 woodpeckers [13,15]. However, the extent to which alternative hypotheses involving mimicry may 283 account for convergence in these groups is largely unknown.…”
mentioning
confidence: 99%